Gaya Komunikasi Pengguna Media Sosial Tiktok dalam Berpendapat Mengenai Kasus Pelecehan Seksual - Hasanah, Adisya Putri; Zuhriah, Zuhriah (Asosiasi Ide Bahasa Kepri, 2024)
This research aims to analyze the communication style of TikTok social media users in expressing opinions regarding cases of sexual harassment. The research method uses a qualitative approach by collecting data through observation of TikTok content related to cases of sexual harassment. This research focuses on analyzing communication styles, including word choice, facial expressions, body movements, and visual elements used by TikTok users. The research results show variations in the communication styles used by TikTok users in conveying their opinions regarding sexual harassment cases. Some users tend to use humor or creative language, while others are more serious and prioritize facts. These findings provide insight into how TikTok users adapt their communication styles to address sensitive issues such as sexual harassment on social media. The implications of this research can be used to understand the dynamics of online communication in the context of relevant social issues.